The Critique of European Nihilism. Interpretation, Responsibility, and Action. (13th May 2014) - Wittrock, Jon; Andrén, Mats
<x content-type="archive" xml:space="preserve">Abstract</x> The concept of 'nihilism' is ambiguous and has had and continues to be attached to several different usages. This special Focus primarily looks at the ways in which 'nihilism', in and following the works of Friedrich Nietzsche, has been understood as specifically tied to a crisis of European culture or civilisation, and has come to be politicised in conjunction with the National Socialist and Fascist movements in Germany and Italy during the twentieth century. Specifically, the individual articles deal with the connection between an understanding of nihilism and what it entails for the question concerning political responsibility. This introductory article presents this thematic, introduces the other contributions, and attempts to situate these debates on nihilism in the context of processes of secularisation. The article retrieves three major themes in relation to the critiques surveyed in this special Focus: nihilism as a crisis of beliefs and values, as an appropriation of religious elements into ideological grand narratives, and as the unshackling of an instrumental approach towards reality, and argues that all of them remain relevant to contemporary debates.